Metal-microbe interactions and microbial bioremediation of toxic metals - Senel, Gülad Uslu; Hanay, Ozge (CRC Press, 2017)
Heavy metals are natural components of the earth’s crust and are widely distributed in the environment, but indiscriminate use in industries for various human purposes has distorted their geochemical cycles and biochemical balance. Industries often release excess amount of heavy metals such as cadmium, copper, lead, nickel, and zinc into natural soil and aquatic environments. Exposure to such heavy metals for a prolonged period may have deleterious effects on human life and aquatic biota. Microorganisms play a crucial role in the remediation of heavy metals by biotransforming them into nontoxic forms. Understanding the biochemical and molecular mechanism of metal accumulation has several biotechnological implications for the restoration of metal-contaminated sites. In view of this, this chapter explores the abilities of microorganisms to resist, accumulate, and transform heavy metals into innocuous forms. This chapter summarizes fundamental insights regarding genetic and molecular basis of metal tolerance in microbes, with special reference to the metal-binding genes involved in tolerance and detoxification. These strategies can be further utilized to overcome the bottlenecks associated with the heavy metal remediation process. © 2017 by Taylor & Francis Group, LLC.